2007
DOI: 10.1111/j.1745-7254.2007.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Wnt3a signaling promotes proliferation, myogenic differentiation, and migration of rat bone marrow mesenchymal stem cells

Abstract: Aim: To investigate the effects of the wingless-related MMTV integration site 3A (Wnt3a) signaling on the proliferation, migration, and the myogenic and adipogenic differentiation of rat bone marrow mesenchymal stem cells (rMSC). Methods: Primary MSC were isolated and cultured from Sprague-Dawley rats and characterized by flow cytometry. Mouse L cells were transfected with Wnt3a cDNA, and conditioned media containing active Wnt3a proteins were prepared. Cell proliferation was evaluated by cell count and 5-brom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 41 publications
(59 reference statements)
5
60
0
Order By: Relevance
“…As shown in several reports, osteogenesis, myogenesis and chondrogenesis are all promoted, while adipogenesis is the only mesenchymal developmental process, which is inhibited by WNT molecules (Zhou et al 2004, 2007, Akimoto et al 2005, Kennell & MacDougald 2005, Kirton et al 2007, Shang et al 2007a,b, Schilling et al 2008. For example, canonical WNT3A signalling in mesenchymal stem cells resulted in the induction of several pro-myogenic factors such as PAX7, MYOD and myogenin.…”
Section: Wnt Molecules In the Determination Of Preadipocytesmentioning
confidence: 99%
“…As shown in several reports, osteogenesis, myogenesis and chondrogenesis are all promoted, while adipogenesis is the only mesenchymal developmental process, which is inhibited by WNT molecules (Zhou et al 2004, 2007, Akimoto et al 2005, Kennell & MacDougald 2005, Kirton et al 2007, Shang et al 2007a,b, Schilling et al 2008. For example, canonical WNT3A signalling in mesenchymal stem cells resulted in the induction of several pro-myogenic factors such as PAX7, MYOD and myogenin.…”
Section: Wnt Molecules In the Determination Of Preadipocytesmentioning
confidence: 99%
“…Wnt signaling also suppresses the induction of Sox9, a key regulator of chondrogenesis, which results in the inhibition of mesenchymal stem cell differentiation to chondrocytes [14,15]. In addition, Wnt signaling upregulates two key regulators of myogenesis, MyoD and Myf 5, in the induction of myogenic differentiation [16].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that Wnt3a induces myogenic differentiation in bone marrow MSCs via the ectopic expression of activated beta-catenin or pretreatment with Wnt3a conditioned medium in vitro [18,19] . In the current study, we hypothesized that Wnt3a would improve the myogenic differentiation efficiency of transplanted MSCs and repair the muscle damage in vivo.…”
Section: Acta Pharmacologica Sinica Npgmentioning
confidence: 99%
“…The medium was then collected, centrifuged at 1000×g for 10 min, and filtered through a nitrocellulose membrane. The abundance of the Wnt3a protein in Wnt3a-CM and L-CM was detected by Western blot analysis [19] . Wnt3a-CM was depleted of the Wnt3a protein by incubation with 4 μg/mL rabbit antiWnt3a antibody (Santa Cruz Biotechnology, Santa Cruz, CA, USA) at 4 °C overnight.…”
Section: Preparation Of Wnt3a-conditioned Mediummentioning
confidence: 99%
See 1 more Smart Citation